Recommendations for whole genome sequencing in diagnostics for rare diseases - Souche, Erika; Beltran, Sergi; Brosens, Erwin; Belmont, John W; Fossum, Magdalena; Riess, Olaf; Gilissen, Christian; Ardeshirdavani, Amin; Houge, Gunnar; van Gijn, Marielle; Clayton-Smith, Jill; Synofzik, Matthis; et al. (European journal of human genetics, 2022)
In 2016, guidelines for diagnostic Next Generation Sequencing (NGS) have been published by EuroGentest in order to assist laboratories in the implementation and accreditation of NGS in a diagnostic setting. These guidelines mainly focused on Whole Exome Sequencing (WES) and targeted (gene panels) sequencing detecting small germline variants (Single Nucleotide Variants (SNVs) and insertions/deletions (indels)). Since then, Whole Genome Sequencing (WGS) has been increasingly introduced in the diagnosis of rare diseases as WGS allows the simultaneous detection of SNVs, Structural Variants (SVs) and other types of variants such as repeat expansions. The use of WGS in diagnostics warrants the re-evaluation and update of previously published guidelines. This work was jointly initiated by EuroGentest and the Horizon2020 project Solve-RD. Statements from the 2016 guidelines have been reviewed in the context of WGS and updated where necessary. The aim of these recommendations is primarily to list the points to consider for clinical (laboratory) geneticists, bioinformaticians, and (non-)geneticists, to provide technical advice, aid clinical decision-making and the reporting of the results.
Keywords: Exome; vysoce účinné nukleotidové sekvenování; Rare Diseases; Whole Genome Sequencing; vzácné nemoci; Polymorphism, Single Nucleotide; genom lidský; exom; Humans; jednonukleotidový polymorfismus; Genome, Human; High-Throughput Nucleotide Sequencing; lidé; sekvenování celého genomu